The origin of slow relaxation following photoexcitation of W7 in myoglobin and the dynamics of its hydration layer - Li, Tanping (2008)
Molecular dynamics simulations are used to calculate the time dependent Stokes shift following photoexcitation of Trp-7 (W7) in myoglobin. In agreement with experiment, a long time (~60ps) component is observed. Since the long time Stokes shift component is absent when we repeat the calculation with protein frozen at the instant of photoexcitation, we firmly establish that protein flexibility is required to observe slow Stokes shift dynamics in this case. A transition between sub-states near the middle of a 30ns ground state trajectory gave us an opportunity to compare solvation dynamics in two different environments. While some of the superficial features are different, we find that the underlying dynamics are shared by the two isomers. It is necessary to look beyond a decomposition of the Stokes shift into protein and water contributions, and probe the underlying dynamics of protein side groups, backbone, and water dynamics to obtain a full picture of the relaxation process. We analyze water residence times, diffusion, and reorientation dynamics in the hydration layer. We find slow components in each of these quantities, and critically examine their origin and how they affect the observed Stokes shift.